2022
DOI: 10.1175/bams-d-21-0214.1
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the Turkana Jet and the East African Dry Tropics: The RIFTJet Field Campaign

Abstract: The Turkana Low-level Jet (LLJ) is an intrinsic part of the African climate system. It is the principle conduit for water vapour transport to the African interior from the Indian Ocean, and droughts in East Africa tend to occur when the jet is strong. The only direct observations of the Turkana Jet come from manual tracking of pilot balloons in the 1980s. Now, modern reanalysis datasets disagree with one another over the strength of jet winds and underestimate the strength of the jet by 25-75% compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Finally, it is noteworthy that the underestimation of the gap flow in the GRV in ERA5 agrees with the underestimation of the Turkana Jet recently found by Munday et al (2022) based on radiosonde observations. Similar to the gap flow in the GRV, the Turkana Jet does not only exhibit a strong diurnal cycle due to the thermal forcing (Munday et al, 2022) but is also affected by synoptic-scale pressure gradients associated with low-level ridging along the East African coast (Vizy and Cook, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, it is noteworthy that the underestimation of the gap flow in the GRV in ERA5 agrees with the underestimation of the Turkana Jet recently found by Munday et al (2022) based on radiosonde observations. Similar to the gap flow in the GRV, the Turkana Jet does not only exhibit a strong diurnal cycle due to the thermal forcing (Munday et al, 2022) but is also affected by synoptic-scale pressure gradients associated with low-level ridging along the East African coast (Vizy and Cook, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Again, this led to differential air mass advection in the lower troposphere. Potentially warmer air from north-eastern Africa was advected towards the Afar Triangle, whereas the Turkana Jet (Nicholson, 2016;Munday et al, 2022) brought potentially colder air into the Turkana Channel and the region around Lake Abaya (Fig. 2b).…”
Section: Synoptic Conditionsmentioning
confidence: 99%
“…However, we note that differences in moisture convergence in the ERA5 reanalysis are not large enough to balance the precipitation differences observed in the IMERG dataset. This is perhaps unsurprising given that ERA5 underestimates the true strength of the Turkana jet (Munday et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The orography of East Africa, shown in Figure 1a, influences the direction and strength of the low‐tropospheric wind (Kinuthia, 1992; Indeje et al ., 2001) and drives spatial rainfall variations (Nicholson, 2017; Vizy and Cook, 2019; Munday et al ., 2021). A key feature of the East African climate that is influenced by orography and has been observed by radiosondes (Kinuthia and Asnani, 1982; Kinuthia, 1992; Munday et al ., 2022) is the Turkana jet, a strong southeasterly low‐level jet at approximately 850 hPa between the Ethiopian Highlands and East African Highlands (Figure 1a). Modelling experiments (Indeje et al ., 2001) and observations of higher jet speeds across narrower parts of the channel (Kinuthia, 1992) suggest a Bernoulli forcing on jet characteristics and that the shape of the Turkana channel controls the low‐level jet's orientation and direction.…”
Section: Introductionmentioning
confidence: 99%
“…This may have some limitations, especially for wind power generation, as previous studies have highlighted potential issues with ERA5 (Bloomfield et al, 2020; Ramon et al, 2019). Using observed data of the Turkana Jet Munday et al, 2022 found that ERA5 underestimates low‐level wind speeds in the Turkana Jet region by around 30%. King et al (2021) shows three different reanalysis products perform quite differently over Kenya; however, the lack of available observational wind data makes it difficult to determine which is most accurate.…”
Section: Discussionmentioning
confidence: 99%